THE QUALITY OF GOVERNMENT REGULATIONS ON COMPANY OPERATIONAL EFFICIENCY: THE MEDIATING ROLE OF PUBLIC SERVICES IN THE BUSINESS READY INDEX - Aleknaek Martua (Fakultas Politik Pemerintahan IPDN, 2025)
Abstract The quality of government regulation is a key factor in creating a conducive business climate and improving corporate operational efficiency. However, the effectiveness of regulation is not only determined by the quality of its normative design, but also depends heavily on the performance of public services as a mechanism for policy implementation. This study aims to analyze the effect of the quality of government regulations on the operational efficiency of companies by placing public services as a mediating variable in the Business Ready Index (B-READY) framework developed by the World Bank. This study uses a quantitative approach by utilizing secondary data from B-READY in 2024 covering 50 countries. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test the direct and indirect relationships between variables. The results of the study indicate that regulatory quality has a positive and significant effect on public service performance, and that public services have a positive and significant effect on corporate operational efficiency. Furthermore, public services are proven to significantly mediate the relationship between regulatory quality and operational efficiency. These findings indicate that quality regulation does not automatically improve operational efficiency without the support of effective, integrated, and responsive public services. Substantively, this study confirms that public services are a key mechanism that translates regulations from the normative level into actual operational practices. The policy implications of this study emphasize the importance of regulatory reform integrated with strengthening public service capacity and digital transformation of government to improve business competitiveness and national economic performance. This research contributes to the development of public policy literature by enriching the conceptual model of the relationship between regulatory quality, public services, and operational efficiency from the perspective of the B-READY. Keywords: Regulatory quality; public services; operational efficiency; B-READY; SEM-PLS